PENGARUH KEPEMIMPINAN, KOMUNIKASI, DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PT.BPR SRIARTHA LESTARI DENPASAR - septiadi, made; supartha, wayan gede (E-Jurnal Manajemen; Vol 2 No 8 (2013), 2013)
Job satisfaction leads to a person's general attitude about his work. So that each individual has a high job satisfaction, every company must pay attention to everything that affects job satisfaction. Leadership, communication, and work environment are some of the factors that influence job satisfaction of employees in the organization. This study aimed to investigate the effect of significant variables simultaneously and partially leadership, communication, and work environment on job satisfaction of employees of PT. BPR Lestari Sriartha Denpasar by taking a sample of 56 individuals are all employees of PT. BPR Lestari Sriartha Denpasar. Based on the test results of F-test, then the variable; leadership, communication, and positive work environment simultaneously significant effect on employee job satisfaction. Judging from the results of t-test, then the leadership variable t (4,308) ? t table (1.671), communication variable t (2,549) ? t table (1.671) and for the work environment variables t (3.618) ? t table (1.671), is a positive and significant effect partially Keywords : Leadership, Communication, Physical Work Environment and Job Satisfaction